2020
DOI: 10.9734/ejmp/2020/v31i1530322
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera Leaf Extract Promotes Antioxidant, Survival, Fecundity, and Locomotor Activities in Drosophila melanogaster

Abstract: Aim: The study was designed to investigate antioxidant, survivability,  fecundity, and locomotor activity of Moringa oleifera leaf (MOL) extract in Drosophila melanogaster. Materials and Methods: The study was conducted at the Africa Centre of Excellence in phytomedicine Research and Development (ACEPRD), University of Jos, Nigeria, in August 2019 - March 2020. In the first place, in vitro analysis of the antioxidant activity of extracts of M. oleifera in various solvents (Aqueous, Methanol-Aqueous co-so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It could be inferred from these results that silymarin has no adverse effects on short-time or chronic therapy. Vahid et al reported that silymarin is safe in humans at a dose of 700mg thrice daily for 24 weeks 19 The climbing assay (Negative geotaxis) has been used to study the effects of chemicals on exercise, locomotion, learning, and memory in the Drosophila melanogaster 20,21 . The increased climbing activity observed in this study indicates silymarin's ability to improve learning and memory, locomotion, orientation, and location in DM after tapping to the bottom.…”
Section: Discussionmentioning
confidence: 99%
“…It could be inferred from these results that silymarin has no adverse effects on short-time or chronic therapy. Vahid et al reported that silymarin is safe in humans at a dose of 700mg thrice daily for 24 weeks 19 The climbing assay (Negative geotaxis) has been used to study the effects of chemicals on exercise, locomotion, learning, and memory in the Drosophila melanogaster 20,21 . The increased climbing activity observed in this study indicates silymarin's ability to improve learning and memory, locomotion, orientation, and location in DM after tapping to the bottom.…”
Section: Discussionmentioning
confidence: 99%
“…Moringa oleifera has been identified as one of the plants with the highest levels of bioactive molecules, such as polyphenols, flavonoids, and tannins, which elicit an antioxidant response [62]. Iorjiim et al [63] reported a significant increase in the activity of antioxidant enzymes glutathione-S-transferase and catalase in Drosophila treated with M. oleifera extract, suggesting its role in enhancing the activity of antioxidant enzymes and reducing the harmful effects of ROS on aging. Likewise, when leaf extracts of M. oleifera were administered to Drosophila at a dose of 5 mg•mL −1 as a dietary supplement, the flies exhibited a remarkable increase in lifespan compared to the control group.…”
Section: Phytochemical Effect On Agingmentioning
confidence: 99%